Going the Way of the Dodo: De-Extinction, Dualisms, and Reframing Conservation - Alejandro E. Camacho (Washington University Law Review, 2015)
De-extinction, a suite of selective breeding or biotechnological processes for reviving and releasing into the environment members or facsimiles of an extinct species, has been the subject of a recent surge of analysis in popular, scientific, and legal literature. Yet de-extinction raises more fundamental questions about the relationship between humans and nature and about the more and less useful ways that the law serves to navigate that relationship. Unfortunately, the endangered species, invasive species, and public land management laws likely to govern the revival and introduction of de-extinct species largely remain premised on an understanding of nature as static and easily divisible from human activity. In these contexts, the law habitually privileges and even actively promotes what it identifies as natural and native over the unnatural and exotic. Through the example of de-extinction, this article illustrates the limitations of the law’s reliance on these crude dualisms. Currently, de-extinct species will often be obstructed as non-native and introduced (even if they might promote ecological function in a particular area) and may be allowed or promoted in locations they used to exist (even if likely to cause ecological damage). De-extinction illustrates how policymakers need to reformulate natural resources law to be less dependent on these strict dualities. Instead, the article argues in favor of cautious risk assessment that acknowledges the dynamism of nature and humanity’s indivisibility from it.
Keywords: De-extinction; Environmental Law; Endangered species; Conservation; Public Land Management Law; Natural Resource Law